2019
DOI: 10.1002/ccd.28413
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of polymer‐free biolimus‐eluting stents versus ultrathin stents in unprotected left main or coronary bifurcation: A propensity score analysis from the RAIN and CHANCE registries

Abstract: Objectives Evaluate safety and efficacy of polymer‐free biolimus‐eluting stents (PF‐BESs) versus ultrathin stents in unprotected left main (ULM) or bifurcation. Background PF‐BESs due to reduced length of dual antiplatelet therapy (DAPT) are increasingly used. However, there are limited data about safety and efficacy for ULM or bifurcation. Methods We selected all‐patients treated for ULM or bifurcation from two multicenter real life registries (RAIN [NCT03544294] evaluating ultrathin stents, CHANCE [NCT036222… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…3,4 In the large scale LEADERS-FREE trial, a polymer-free biolimuseluting stent (PF-BES) demonstrated improved outcomes as compared to a bare metal stent in high bleeding risk (HBR) patients, when used with a 1-month DAPT strategy. 5 The favorable clinical profile of the PF-BES was further established across a wide range or real-world patients, with outcomes in the lower range of cardiovascular adverse event rates observed with contemporary new-generation drug-eluting stents (DES) when used in patients with mostly non-HBR features, [6][7][8][9] and overall good safety and efficacy when used in patients with mostly HBR features. 10 The PF-BES peculiar characteristics, including the absence of a polymer-coat along with the fast drug elution, may result in rapid and complete stent endothelialization, blunting the late ST risk observed with polymer-coated DESs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 In the large scale LEADERS-FREE trial, a polymer-free biolimuseluting stent (PF-BES) demonstrated improved outcomes as compared to a bare metal stent in high bleeding risk (HBR) patients, when used with a 1-month DAPT strategy. 5 The favorable clinical profile of the PF-BES was further established across a wide range or real-world patients, with outcomes in the lower range of cardiovascular adverse event rates observed with contemporary new-generation drug-eluting stents (DES) when used in patients with mostly non-HBR features, [6][7][8][9] and overall good safety and efficacy when used in patients with mostly HBR features. 10 The PF-BES peculiar characteristics, including the absence of a polymer-coat along with the fast drug elution, may result in rapid and complete stent endothelialization, blunting the late ST risk observed with polymer-coated DESs.…”
Section: Introductionmentioning
confidence: 99%
“…Results: Following PF-BES-PCI, 328(40.3%) and 485(59.6%) patients were discharged with 1-month and longer DAPT (12 months [6][7][8][9][10][11][12]), respectively. Patients with a previous or index MI were less likely to be discharged on 1-month DAPT.…”
mentioning
confidence: 99%
“…In a pooled analysis of 2 registries for left main and bifurcation lesions, CHANCE, using polymer-free biolimus-eluting stent (PF-BES) and in RAIN using 2nd-generation DES with a strut thickness of approximately 80 μm (ultra-thin DES) (Table ), 1-month DAPT after PCI using the ultra-thin DES resulted in more frequent ischemic events than when using PF-BES (22% vs. 12%, P=0.04). 9 A substudy of bifurcation lesions was conducted in the GLOBAL LEADERS using PF-BES with a randomized comparison between 1-month DAPT plus 23-month monotherapy of ticagrelor and 12-month conventional DAPT plus 12-month monotherapy of aspirin (Table ). The substudy included a large number of 2-stenting cases (489 patients), which led to a higher composite endpoint of death and new-onset Q-MI than with the 1-stent treatment (7.2% vs. 4.0%, P=0.008), and treatment with 1-month DAPT followed by monotherapy with ticagrelor resulted in less ST compared with conventional DAPT treatment (HR 0.46, 95% CI 0.22-0.97).…”
mentioning
confidence: 99%